Designing AI-Based 3D Animation to Inspire Young Entrepreneurs at Bina Bangsa - Wahyudin Wahyudin; Nurhasan Nugroho; Ahmad Munawir (Brilliance: Research of Artificial Intelligence, 2025)
Digital transformation presents significant opportunities to develop young entrepreneurship. However, many university students and novice MSME (Micro, Small, and Medium Enterprises) actors still face barriers such as limited digital literacy and access to relevant information. This study aims to design and produce an AI-based 3D animated educational film as a medium to inspire and foster the entrepreneurial spirit among students. The development process follows the Multimedia Development Life Cycle (MDLC) method, which includes six stages: concept, design, material collecting, assembly, testing, and distribution. Several Artificial Intelligence (AI) technologies were utilized throughout the production, including ChatGPT for scriptwriting, Sora and LTX Studio for scene visualization, ElevenLabs for text-to-speech synthesis, Hedra for automatic lipsyncing, Suno AI for background music generation, and CapCut for final video editing. The final product is an 18-minute animated film titled "Langkah Pertama" (The First Step), which narrates a fictional story of university students who support local MSMEs through digital innovations. Initial evaluations involving targeted student audiences suggest that the film is effective as both an educational and motivational tool. It visually conveys key entrepreneurial values while emotionally engaging viewers. The results of this study demonstrate that AI can be practically applied in multimedia-based learning content development, even within limited production environments. This approach provides a scalable, innovative way to enhance entrepreneurship education in the digital age.